1981
DOI: 10.1111/j.1399-3011.1981.tb03000.x
|View full text |Cite
|
Sign up to set email alerts
|

SYNTHESIS OF THYMOSIN β4

Abstract: 4. Heyes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

1982
1982
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 9 publications
0
5
0
3
Order By: Relevance
“…Previously reported nonclinical studies suggest that Tβ4 may have the biological properties found useful clinically in these patient populations. Tβ4 is a highly conserved naturally occurring, water‐soluble peptide 2,3 . In addition to being found in a majority of tissues and cell types, it is also found in the blood, and in other body fluids, including wound fluids, tears, saliva, and cerebrospinal fluid 4–6 .…”
Section: Tβ4 Activities In Woundsmentioning
confidence: 99%
“…Previously reported nonclinical studies suggest that Tβ4 may have the biological properties found useful clinically in these patient populations. Tβ4 is a highly conserved naturally occurring, water‐soluble peptide 2,3 . In addition to being found in a majority of tissues and cell types, it is also found in the blood, and in other body fluids, including wound fluids, tears, saliva, and cerebrospinal fluid 4–6 .…”
Section: Tβ4 Activities In Woundsmentioning
confidence: 99%
“…T β 4 protein is therefore likely to have increasing importance as a therapeutic agent, which in turn suggests that there will be an increasing demand for T β 4 production. Currently, the T β 4 is produced commercially by two approaches: extraction from animal thymus [1] and chemical synthesis [25], but there are challenges with meeting clinic demand due to risks of zoonosis and higher production costs [25, 26]. …”
Section: Discussionmentioning
confidence: 99%
“…It was suspected that thymosin β 4 would be an important immunomodulatory factor influencing maturation of T‐lymphocytes. Therefore, the acetylated tritetracontapeptide was synthesized already in 1981 by automated solid phase synthesis 3 . Because thymosin fraction V consisted of many major and minor peptides a nomenclature was proposed based on the isoelectric points of the various sequenced peptides.…”
Section: The β‐Thymosin Familymentioning
confidence: 99%
“…Therefore, the acetylated tritetracontapeptide was synthesized already in 1981 by automated solid phase synthesis. 3 Because thymosin fraction V consisted of many major and minor peptides a nomenclature was proposed based on the isoelectric points of the various sequenced peptides. Peptides with isoelectric points below 5 were termed ␣-thymosins (highly acidic) and those with isoelectric points between 5 and 7 (acidic) were named ␤-thymosins.…”
Section: The β-Thymosin Familymentioning
confidence: 99%